\(60\%x+1,5x=\frac{1}{6}.\frac{2}{3}+\frac{1}{6}.\frac{1}{3}\)
\(60\%x+1,5x=\frac{1}{6}\left(\frac{2}{3}+\frac{1}{3}\right)\)
\(60\%x+1,5x=\frac{1}{6}.1\)
\(60\%x+1,5x=\frac{1}{6}\)
\(\frac{60}{100}x+1,5x=\frac{1}{6}\)
\(\frac{3}{5}x+1,5x=\frac{1}{6}\)
\(x\left(\frac{3}{5}+1,5\right)=\frac{1}{6}\)
\(\frac{21}{10}.x=\frac{1}{6}\)
\(\Rightarrow x=\frac{5}{63}\)
\(60\%.x+1,5.x=\frac{1}{6}.\frac{2}{3}+\frac{1}{6}.\frac{1}{3}\)
\(\frac{60}{100}.x+1,5.x=\frac{1}{6}.\left(\frac{2}{3}+\frac{1}{3}\right)\)
\(\frac{3}{5}.x+\frac{15}{10}.x=\frac{1}{6}.\frac{3}{3}\)
\(x+\left(\frac{3}{5}.\frac{15}{10}\right)=\frac{1}{6}.1\)
\(x+\left(\frac{3}{1}.\frac{3}{10}\right)=\frac{1}{6}\)
\(x+\frac{9}{10}=\frac{1}{6}\)
\(x=\frac{1}{6}-\frac{9}{10}\)
\(x=\frac{10}{60}-\frac{54}{60}\)
\(x=\frac{-44}{60}\)
\(x=\frac{-11}{15}\)